Derivations in Banach algebras - Kyoo-Hong Park; Yong-Soo Jung; Jae-Hyeong Bae (International Journal of Mathematics and Mathematical Sciences)
We present some conditions which imply that a derivation on a Banach algebra maps the algebra into its Jacobson radical.